(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
Abu Rusheid area forms a NW-SE antiformal structure and it is The present study aims to improve the antioxidant and antimicrobial truncated by a major fault in the north-west along wadi sikeit. Granitic properties of cake and produce low calorie cake through substitution of gneisses rocks are cross cut by NNW-SSW trending altered and mineral wheat flour (WF) by irradiated broccoli (Brassica oleracea L.var italica) ized shear zone. The study area is bounded by longitude 34º 48´ 34º 48´ powder. In this study broccoli heads powder and broccoli leaves pow 30´´E and latitude 24º 37́ 24º 38´N. This study aims to define sources and der were gamma irradiated at dose levels of 0, 3, 5 and 7 kGy. Results distribution of rare earth elements (REEs) and to describe the geochemi showed that ethanolic (70%) extract of irradiated broccoli heads powder cal processes that govern mobility of U and valuable radioelements, (IBHP) and irradiated broccoli leaves powder (IBLP) at a dose level of 5 which comes from leaching ofmore labil REEs bearing minerals of gra kGy had higher total phenolic compounds (TPC) and antioxidant activ nitic gneisses rocks, cut by mineralized shear zone and green silicates ity (AOA) compared to control and other doses. Thus,IBHP and IBLP mainly amphiboles (hornblende).And mineralization extension accord at dose level of 5 kGy were selected for fortificationof cake. IBHP was ing to grain sizes in trace elements.